La falta de inclusión laboral de los trabajadores de la economía informal del reciclaje evidencia la ausencia de apoyo de organismos públicos en la ciudad de Loja, propuesta de mejoramiento - González Elizalde, Sonia Francisca (2016)
The research aims to determine the level of compliance with of local government agencies in the regulation of the work of the informal recycling in the city of Loja; He was carried out a diagnosis of the current state of the work of the informal recycling in the city and public bodies that have direct competition andcan give inter-agency support access to decent, stable, work with fair pay is a duty and a right that we have the Ecuadorian, is a priority for the State of Ecuador as well as the Constitution. You could also be that interested persons who engage in the activity of recycling, counting with labour, social and economic stability that allows them access to a better quality of life. Determines the perception of local public bodies in the city of Loja; in what refers to the work of the informal recycling in the town, in what would have or not competencies, or if they could coordinate actions and contribute to the Betterment of this part of the population as vulnerable by the current situation in which are doing the activity of recycling. Analyzed information was identified, that in the city of Loja there are pickers who continue making recycling activity; in our town, in containers arranged in different places of the city and the landfill's streets; doing it in inadequate conditions where expose your health contaminated materials. In the case of the city of Loja is not doing anything by the public agencies regulate and control this type of informal work in our city.